2018
DOI: 10.1111/hiv.12667
|View full text |Cite
|
Sign up to set email alerts
|

A structural equation model to predict pre‐exposure prophylaxis acceptability in men who have sex with men in Leicester, UK

Abstract: The results reveal socio-economic inequalities in HIV knowledge and HIV testing, and suggest that MSM who have high levels of HIV knowledge and perceived HIV risk and who regularly test for HIV are most likely to endorse PrEP as personally beneficial. HIV knowledge and accurate risk appraisal should be promoted in MSM. The HIV testing context constitutes an ideal context for promoting PrEP to high-risk MSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…While Study 1 indicates that those who are less adherent to preventive activity are also less likely to test for COVID-19, Study 2 provides additional evidence that they are also less likely to seek vaccination. This would appear to be consistent with the concept of the ‘prevention norm’ which is shared and reinforced by members of a community (see also Jaspal et al, 2019 ) and with recent research showing the negative correlation between loneliness and vaccination likelihood due to decreased exposure to the social norm of vaccination (Hajek & König, 2019 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…While Study 1 indicates that those who are less adherent to preventive activity are also less likely to test for COVID-19, Study 2 provides additional evidence that they are also less likely to seek vaccination. This would appear to be consistent with the concept of the ‘prevention norm’ which is shared and reinforced by members of a community (see also Jaspal et al, 2019 ) and with recent research showing the negative correlation between loneliness and vaccination likelihood due to decreased exposure to the social norm of vaccination (Hajek & König, 2019 ).…”
Section: Discussionsupporting
confidence: 87%
“…In the context of HIV, it has been found that people who engage with HIV testing are also more likely to endorse other novel approaches to preventing infection, such as pre-exposure prophylaxis (Jaspal et al, 2019 ). This could be attributed to an overall ‘prevention norm’, which motivates members of a collective to endorse and comply with particular preventive behaviors that are socially represented as being desirable or even necessary in a risk context.…”
Section: Introductionmentioning
confidence: 99%
“…pre-exposure prophylaxis), in that those who perceive themselves to be at either moderate or high risk of HIV infection are more likely to test for HIV and to express interest in PrEP. 15,16,17 Perceived HIV risk can fluctuate over time in accordance with social contextual factors, such as relationships, behavioural 'phases', episodic engagement in substance use and sex work. 18 HIV risk perception is in part determined by social psychological variables.…”
Section: Hiv Risk Perceptionmentioning
confidence: 99%
“…A recent meta-analysis [24] exhibited an overall acceptance rate of 58.7% among gay men and, in the UK, it has been shown that 64% of HIVnegative gay men attending sexual health clinics perceived PrEP as personally beneficial [25] . Higher educational attainment is a strong proxy for PrEP endorsement among gay men -higher rates of PrEP use are observable in those achieving education to a postgraduate level or above [26,27] . Moreover, younger gay men are more likely than older gay men to use PrEP, suggesting that attitudes are more favourable in younger men [28] .…”
Section: Prep Acceptability Among Gay Menmentioning
confidence: 99%